Effectiveness of the ETLE Mobile Unit of Turjawali Satlantas Magetan Police for Law Enforcement Against Traffic Violations - Darmawan, Adam Deva (Advances in Police Science Research Journal, 2024)
Motorized vehicles are known to have many benefits that can make life easier for society in carrying out community activities. However, as the number of motorized vehicles in Indonesia increases increasing the chances of more traffic violations occurring. This is no exception Magetan Police jurisdiction. Meanwhile, conventional ticketing is considered less effective So an online ticketing system was formed called ETLE (Electronic Traffic Law Enformance) ETLE is expected to make fines assessed by the public more transparent. But because using society's machines has no deterrent effect. This research aims to find out implementation, contributing factors, and effectiveness of ETLE Mobile in the jurisdiction Magetan Police. As an analytical tool, the author uses several concepts and theories, namely: theory POAC management, 4 M management element theory and effectiveness theory, law enforcement concepts, concepts taking action against traffic violations, the ETLE Mobile concept. With the research area at Magetan Police. This research was conducted with a qualitative approach, using field research, as well Data collection techniques using observation, interviews and document study.